# Cayley Hamilton Theorem

### History of Cayley-Hamilton Theorem

Hamilton Theorem was proved in the year 1855 in terms of a linear function of the quaternion, a non-commutative ring by Cayley-Hamilton. This theorem persists for general quaternion matrices. This complies with the specific illustration of certain real 4×4 matrices over 2×2 complex matrices. Cayley–Hamilton stated Hamilton Theorem for 3×3 small matrices, but able to publish a proof for the 2×2 case. The general case was initially verified by Frobenius in 1878.

### Hamilton Theorem Proof

The Hamilton theorem states that if matrices A will be replaced instead of x in polynomial, p (x) = det (xln- A), it will give away the zero matrices, such as

P (A) = 0

The theory states that the nxn matrix is eradicated by its characteristic polynomial det (ti- a) which is monic of degree n. The power of A is found by replacing the power of x, which is identified by recurrent matrix multiplication, the constant term of p(x) yields a multiple of the power A₀, which power is indicated as identity matrix. This theorem permits Aᶯ to be considered as a linear combination of matrix power of A. If the ring is assumed as a field, the Cayley–Hamilton theorem would be equal to the statement which states that the smallest polynomial of a square matrix will be divided by its characteristic polynomial.

### Cayley-Hamilton Theorem Example

Here you can see, Cayley-Hamilton theorem example based on Cayley-Hamilton Theorem proof which is stated above.

Example- If A is 3×3 matrix, then is characteristics equation would be considered as

=  │A-λI│ = 0

= λ³ + C1 λ2 + C2λ + C3I

= Substituting λ with A

= A³ +C1A2 + C2A + C3I

Explanation –

Let us consider A as n×n as a square matrix, then its characteristics polynomial will be stated as:

P (λ) =│A-λ In │ = 0

In = Identity matrix similar order as A

According to the Hamilton theorem:

P (A) = 0

Here 0, signifies the zero matrices of same order A

### Quiz Time

1.  The Cayley-Hamilton theorem proof deals only with

a)     Inverse Matrix

b)     Square Matrix

c)      Identity Matrix

d)     Orthogonal Matrix

2.   The number of rows and columns in the square matrix is

a)     More than 10

b)     Similar

c)      Multiples of each other

d)     Different

3.  Find characteristic polynomials, if the 2×2 matrix has 2 and 3 in the first row, 0 and 1 in the second row.

a) λ² – 3 λ + 2

b) λ² + 2

c)  λ² + 3

d) λ² – 2 λ + 3

### Fun Facts

• The Cayley-Hamilton theorem was initially proved in the year 1853, in the form of the inverse of linear equation by a quaternion, a non -commutative ring through Hamilton
• The result of the theory was first verified by Frobenius in the year 1878.
• The first record of the Cayley-Hamilton theorem was accidentally created by William Rowan Hamilton in his book “Lectures on Quaternions”.
• Arthur Cayley in 1858 applied Hamilton theory in the world of the matrix.
• The expected results can be seen when the same theory is applied by Cayley in the matrix of size 3×3. Thus the Cayley-Hamilton theorem was discovered.

1.What is Known as Characteristics Polynomial in Hamilton Theorem?

A. The characteristic polynomial is a polynomial that gives information about the matrix. It is closely associated with the determinant of the matrix and the roots of the characteristic polynomial are eigenvalues of a matrix.

The characteristics equation of the characteristics polynomial sets the matrix equation to zero.

The characteristics polynomial P(x) of an n×n matrix M is given in the below equation:

P(x) = det (xI –M)

I in the above equation denote the identity Matrix.

Two matrices M and N will be considered identical if there exists a Matrix A such that  N=A-1MA

=det (xI –M) = det (A-1 A) det (Xi –M)

= det (A-1) det (xI –M) det (A)

=det (A-1 xIA- A – A-1 MA)

=det(x A-1 A-N)

=det (Xi –N)

Hence and N are similar characteristics polynomial

2. State and Prove Cayley-Hamilton Theorem

A. Cayley-Hamilton theorem states that a matrix agrees with its own equation. If the characteristics equation of an n×n matrix A will be λᶯ + aᶯ‾1 λᶯ‾1 + a₁ λ +a₀ = 0, then

Aᶯ + an-1 A‾1 +…… + a₁A +a₀I = 0

Now we will prove the above theorem with an example:- will be updated soon